INDONESIAN STUDENTS â€œCOMPOSITES TEND TO COMPLEMENTâ€: AN ERROR ANALYSIS - LESTARI, DIAN (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
This is a comprehensive research on the case of how indonesian students study â€œComposites tend to complementâ€. It summarizes the types of discrepancy that Indonesian students make and come up with some corresponding teaching suggestions